Caesarean scar endometriosis: a rare site of extrapelvic endometriosis - Bagchi, Sipra; Gupta, Ashish K.; Alwadhi, Kimmi; Sah, Shanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Scar endometriosis is a rare presentation of extrapelvic endometriosis. A caesarean section scar is the most common site. The typical clinical presentation is that of a palpable firm subcutaneous nodule near surgical scars associated with cyclic pain and swelling during menses. It is often misdiagnosed with other abdominal wall and scar related pathological conditions. Diagnosis is mainly based upon a high index of suspicion. USG with color Doppler can clinch the diagnosis in patients with typical clinical features. FNAC may be inconclusive. MRI is the most sensitive but expensive modality to make the diagnosis. Wide local excision is the treatment of choice. We report a case of caesarean scar endometriosis and discuss about incidence, pathophysiology, diagnosis and treatment of this condition.